PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS MEDIA KOMPUTER VIRTUAL DAN VIDEO DALAM MODEL PEMBELAJARAN LANGSUNG (STUDI PADA MATA DIKLAT INSTALASI SISTEM OPERASI JARINGAN DI SMKN 2 TARAKAN) - Suheriyanto, Suheriyanto; Basuki, Ismet (PENDIDIKAN VOKASI:TEORI DAN PRAKTIK, 2014)
AbstractThis research is based on the lack of information technology which is used at SMKN 2 Tarakan, especially the use of virtual computer and video. Therefore, the learning set which adapt those technology and appropriate learning model are needed. This research develops a learning set which use virtual computer and video in the direct learning of Network Operating System Installation Subject at SMKN 2 Tarakan. This research aims to find out the quality and the effectiveness of learning set which are developed.There are four steps which are conducted. They are preliminary study, design, validation and revision, and empirical test and revision. Those step are adapted from R & D research designed by Borg and Gall. It is also adapted from 4D instructional model by Thiagarajan. The data collecting techniques used are observation, interview, documentation, review, validation, test, and non-test. The data analysis technique is descriptive analysis.The first result of the research is the quality of the learning set gets the average score 3.78. This is based on the logic scoring from the experts. The criterion of the learning set is excellent or very valuable. This scoring used the valid and reliable instruments. The score of the validity is 3.85. The criterion is excellent and its reliability coefficient is 0.92. Its criterion is almost perfect aggrement. The second result is the effectiveness of the learning set through empirical test. The learning runners score is 3.90. Its criterion is excellent. the student competencies achievement score is 3.55. Its criterion is excellent. The average score of both are 3.73 which has excellent as the criteria. Therefore, the conclusion of the research is that the learning set is very effective. The result of data analysis shows that: (1) the learning set has a very good quality because it has been validated using the logic scoring by the experts with valid and reliable instruments and (2) the use of learning set is very effective.Keywords: Learning Set, Virtual Computer, Video, Direct Learning.